Optimalisasi Peran Sekretariat DPRD Kota Cilegon dalam Memfasilitasi Fungsi Pengawasan - Adi Nur fajri; Mohamad Ikrom Arasid; Suherman Suherman (Lembaga Pengembangan Kinerja Dosen, 2025)
The role of the Regional People's Representative Council (DPRD) Secretariat is crucial in supporting the effective supervision function of the DPRD as a pillar of good governance. However, at the Cilegon City DPRD Secretariat, this role faces significant constraints due to a policy of assigning staff to assist in work visits that is not competency-based, which risks weakening local government accountability. This research aims to analyze the facilitation role of the Cilegon City DPRD Secretariat, identify the constraints arising from the removal of expert supervision staff, and formulate optimization strategies to strengthen the institution's role. This study uses a qualitative descriptive method, with data collected through in-depth interviews with key informants within the Secretariat, observation, and document analysis. The research findings indicate that (1) the Secretariat's role has been degraded to be administrative rather than substantive; (2) the main constraint stems from a staff assignment system that ignores competence, which leads to a decline in the quality of supervision reports; and (3) there is an urgent need to reform the human resource management (HRM) system. It is concluded that the optimization of the Secretariat's role can only be achieved by reforming the staff assignment policy and implementing structured competency development programs to restore professionalism and effective support for the DPRD's supervision function. Therefore, this research recommends three strategic steps: in the short term, revising the staff assignment policy to prioritize competence; in the medium term, developing and implementing clear Competency-Based HRM Guidelines; and in the long term, organizing continuous functional training programs to enhance staff capacity in professionally and effectively supporting the DPRD's supervision function.